Survei Kebugaran Jasmani Masyarakat yang Memanfaatkan Alun-alun Simpang Enam Demak untuk Aktivitas Fisik - Maulina, Alya; Kusuma, Donny Wira Yudha (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study is to determine the condition of physical fitness and public health who use Simpang Enam Demak Square as a forum for Physical Activity. This research is quantitative research with a descriptive approach. Using the technique of cross sectional study method. Incidental/Accidental Sampling Techniques. Data collection techniques use observation, documentation, tests and measurements. The data analysis used is descriptive percentage. By conducting tests and measurements, namely physical fitness (test up and down the bench / harvard step test) and measuring tension (blood pressure). Based on the results of a study conducted with 150 respondents obtained data, most of the respondents were in the good category of 65 respondents 45%. The results of blood pressure measurement showed that 128 (85%) repondents had normal blood pressure. From the calculation of the age of 17-18 th 41%, 19-21 th 23%, 21-23 th 35%. From the calculation of gender Male 56%, and female 44%. From the statistical test, the value of rs= 0.482 was obtained. The conclusion of this study is that good physical fitness and normal blood pressure will make a positive value for a person in doing physical activity.